Electrochemical and Optical Spectroscopic Probing of Transition‐Sized Au130(SR)50 Nanoclusters - Xiangsha Du; Xinwen Zhang; Hedi Ma; Meng Zhou; Tatsuya Higaki; Gangli Wang; He Wang; Rongchao Jin (ChemElectroChem, 2024)
Abstract Ultrasmall metal nanoclusters (NCs) exhibit a quantized conduction band, hence, a distinct HOMO‐LUMO gap (Eg). Such a quantized electronic structure gives rise to multiple discrete peaks in the optical absorption spectrum of the NCs. As the size grows to 130 gold atoms (Au130 protected by ligands), electrical charging and optical behaviors seem to show certain metal‐like features (hence, transition‐sizes). To probe such behaviors, especially the potential ligand effect, we have devised the synthesis of Au130 NCs protected by phenylethanethiolate and naphthalenethiolate, respectively, with the former having a nonconjugated separation between the aromatic molecular group and the metal core while the latter being in direct bonding. A careful comparison of these two Au130 nanoclusters with the earlier reported analogues is carried out, including the structurally characterized Au130(pMBT)50 and the aqueous counterpart. While all of these nanoclusters possess the same 80 free electron counts in the core, some notable differences in electrochemical and optical properties are found, which are attributed to the ligand effects. The obtained insights may stimulate further interest in the transition‐sized nanoclusters and also promote their applications in optics, energy conversion, and biomedicine.